Outcomes in acute pulmonary embolism and their association with adherence to international recommendations around COVID-19 pandemic-induced hospital-strain: The experience in a Mexican tertiary care center - Juan José Rodríguez-Crespo; Eduardo Gutiérrez-León; Pedro Dammann-Beltrán; Jurhiat Alejandro Seaman-Gómez; Sergio Contreras-Garduño; Erick Yasar Zúñiga-González; José Guillermo Domínguez-Cherit; Thierry Hernández-Gilsoul; José de Jesús Vidal-Mayo; Fausto Alfredo Ríos Olais; Raúl Rivera Moscoso; Jorge Oseguera Moguel; et al. (PLoS ONE, 2026)
Background Lack of adherence to international recommendations leads to worse outcomes. During the COVID-19 pandemic, the total number and proportion of hospitalized patients increased, consequently straining hospital care and hindering adherence. Aims To evaluate adherence to clinical guidelines at our center, before, during, and shortly after the COVID-19 pandemic-induced hospital strain, and its association with clinical outcomes, using a random, balanced retrospective cohort. Design A balanced and randomized sample of 50 patients per year between 2019 and 2022 was drawn from electronic medical records and analyzed with multivariable and logistic regression models. The primary outcome was a composite of in-hospital death, hemodynamic decompensation within the first 7 days, and in-hospital bleeding. Results The global non-adherence in our study was 45.4%. The main risk factors for non-adherence were any mortality risk classification above low-risk PE and a PESI class different from class I, with ORs of 3.47 (95% CI 2.07–5.82) and 1.57 (95% CI 1.04–2.37), respectively. In both periods (COVID-19 season and non-COVID-19 season), non-adherent management strongly correlated with the composite outcome, OR = 2.36 (95% CI, 1.23–4.54). Non-adherence was also associated with worse in-hospital outcomes, with an incidence rate of the composite outcome of 21.08 per 1000 days/person (95% CI 10.97–40.51) and 47.7 per 1000 days/person (95% CI 33.39–67.50), and an attributable risk of 1.09% (95% CI −8.47%−10.64%). Conclusions Overall, our findings highlight the need to prioritize human and material resources to ensure adherence to the standards of care for PE patients.